2017
DOI: 10.1371/journal.pone.0177662
|View full text |Cite
|
Sign up to set email alerts
|

Network based stratification of major cancers by integrating somatic mutation and gene expression data

Abstract: The stratification of cancer into subtypes that are significantly associated with clinical outcomes is beneficial for targeted prognosis and treatment. In this study, we integrated somatic mutation and gene expression data to identify clusters of patients. In contrast to previous studies, we constructed cancer-type-specific significant co-expression networks (SCNs) rather than using a fixed gene network across all cancers, such as the network-based stratification (NBS) method, which ignores cancer heterogeneit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…NetNorM normalizes patient mutation profiles based on gene network topology, adding or removing mutations for particular patients conditional on the distribution of mutations on the network [98] instead of network smoothing to overcome the sparse and binary nature of mutation data. NBS or similar approaches have successfully stratified cancer cohorts into subtypes that are related to clinical outcomes such as patient survival, response to therapy or tumor histology in ovarian, lung [97], colorectal, head and neck, kidney [99], endometrial [97,99,100] and prostate cancers [101].…”
Section: Network Analysis Across Tumor Cohortsmentioning
confidence: 99%
See 1 more Smart Citation
“…NetNorM normalizes patient mutation profiles based on gene network topology, adding or removing mutations for particular patients conditional on the distribution of mutations on the network [98] instead of network smoothing to overcome the sparse and binary nature of mutation data. NBS or similar approaches have successfully stratified cancer cohorts into subtypes that are related to clinical outcomes such as patient survival, response to therapy or tumor histology in ovarian, lung [97], colorectal, head and neck, kidney [99], endometrial [97,99,100] and prostate cancers [101].…”
Section: Network Analysis Across Tumor Cohortsmentioning
confidence: 99%
“…It has recently been suggested that interpatient heterogeneity could be better overcome by using cancer-type-specific networks. To this end, He et al [100] employed expression data to create cancer-type-specific significant co-expression networks (SCNs) that were then used with somatic mutation data in an NBS approach. By focusing on the disease-specific network, it was possible to identify survival-associated subtypes in uterine corpus endometrial carcinoma (UCEC) cancer that were not detected by the original NBS method.…”
Section: Network Analysis Across Tumor Cohortsmentioning
confidence: 99%
“…However, gene-gene networks vary from tissue to tissue and a single set of canonical gene-gene networks as prior knowledge may omit or overemphasize some interactions [9]. To address this issue, other studies have elected to use cancer-specific co-expression networks based on RNA expression data [10] or canonical pathways [11].…”
Section: Introductionmentioning
confidence: 99%
“…An example of such network based methods is network smoothing, which fuses network structure with prior knowledge, and produces a measure for each node that respects both the input data and the structure of the network [12]. Such smoothing methods are widely used, with applications ranging from identification of cancer genes [13, 14], identification of gained/lost cellular functions [15] and more [12].…”
Section: Introductionmentioning
confidence: 99%